Incentive spirometry as a way to prevent pulmonary atelectasis development - Kuzmenko, T. S.; Vorotyntsev, S. I.; Кузьменко, Тетяна Сергіївна; Воротинцев, Сергій Іванович; Воротынцев, С. И. (Запорізький державний медичний університет, 2019)
The purpose. The purpose of this study was to evaluate the effectiveness of incentive spirometry (IS) as a method of atelectasis prevention in patients with moderate or high risk of PPCs development after upper abdominal surgery. Materials and methods. The study consisted of two stages. The first retrospective stage was to analyze the medical histories data of 51 inpatients, who were included in the comparison group. The prospective part of the study included 39 patients of the study group, who had sessions of the IS during the first 7 days of the postoperative period. Patients of both groups were operated on the upper abdominal organs by open procedure, operation time was more than 2 hours, all patients had an ARISCAT score ≥26 points. Pulmonary atelectasis development was monitored in the groups in the first week of the postoperative period. The statistical analysis of the data was performed using the Microsoft Excel 2013 and Statistica for Windows 6.0 programs. When comparing the groups according to the clinical outcome, the relative risk (RR) and odds ratio (OR) were determined and then confidence intervals (95 % CI) were calculated. Statistical significance of the results was determined depending on the CI values. Results. During the first 7 days, 34 cases of pulmonary atelectasis (67 %) were recorded in the comparison group. In the study group, 9 patients (23 %) were diagnosed with pulmonary atelectasis. The analysis of clinical results showed that when applying incentive spirometry, there was a statistically significant decrease in the relative risk of atelectasis development within the first week of the postoperative period (RR = 0.346, 95 % CI [0.189; 0.634], P = 0.0006). The odds ratio of atelectasis development in the study group was statistically lower than in the group of retrospective study (OR = 0.150, 95 % CI [0.058, 0.386], P = 0.0001). Conclusions. Incentive spirometry is an effective way to prevent pulmonary atelectasis in patients with a moderate or high risk for developing postoperative pulmonary complications according to the ARISCAT scale after upper abdominal surgery. Мета роботи – оцінити ефективність спонукальної спірометрії (СС) як способу запобігання розвитку ателектазів легень у пацієнтів із помірним або високим ризиком розвитку післяопераційних легеневих ускладнень (ПЛУ) після оперативних втручань на верхньому поверсі черевної порожнини. Матеріали та методи. Дослідження складалося з двох етапів. Перший, ретроспективний етап, полягав в аналізі історій хвороби 51 стаціонарного хворого (група порівняння). Група дослідження – 39 пацієнтів проспективної частини дослідження, яким у перші 7 днів післяопераційного періоду проводили сеанси СС. Пацієнти обох груп прооперовані відкритим способом на органах верхнього поверху черевної порожнини тривалістю понад 2 години та мали оцінку за шкалою ARISCAT ≥26 балів. У групах відстежували розвиток ателектазів легеневої тканини в перший тиждень післяопераційного періоду. Статистичне опрацювання виконали за допомогою програм Microsoft Excel 2013 та Statistica for Windows 6.0. При порівнянні груп за клінічним результатом визначали відносний ризик (ВР), відношення шансів (ВШ), для них розраховували довірчі інтервали (95 % ДІ). Залежно від значень ДІ визначали статистичну значущість результатів. Результати. Протягом перших 7 днів у групі порівняння зафіксували 34 випадки ателектазування легень (67 %). У групі дослідження ателектази легеневої тканини виникли у 9 пацієнтів (23 %). Аналіз клінічних результатів показав, що при застосуванні СС відбувається статистично значуще зниження відносного ризику розвитку ателектазів у перший тиждень післяопераційного періоду (ВР = 0,346, 95 % ДІ [0,189; 0,634], р = 0,0006). Відношення шансів розвитку ателектазів у групі дослідження статистично значуще нижче порівняно з групою ретроспективної частини дослідження (ВШ = 0,150, 95 % ДІ [0,058; 0,386], р = 0,0001). Висновки. Спонукальна спірометрія є ефективним способом профілактики ателектазування легеневої тканини у пацієнтів із помірним або високим ризиком розвитку післяопераційних легеневих ускладнень за шкалою ARISCAT після оперативних втручань на верхньому поверсі черевної порожнини. Цель работы – оценить эффективность побудительной спирометрии (ПС) как способа предупреждения развития ателектазов легких у пациентов с умеренным или высоким риском развития послеоперационных легочных осложнений (ПЛО) после оперативных вмешательств на верхнем этаже брюшной полости. Материалы и методы. Исследование состояло из двух этапов. Первый, ретроспективный этап, заключался в анализе данных историй болезни 51 стационарного больного (группа сравнения). Группу исследования составили 39 пациентов проспективной части исследования, которым в первые 7 дней послеоперационного периода проводили сеансы ПС. Пациенты обеих групп прооперированы открытым способом на органах верхнего этажа брюшной полости продолжительностью более 2 часов и имели оценку по шкале ARISCAT ≥26 баллов. В исследуемых группах отслеживали развитие ателектазов легочной ткани в первую неделю послеоперационного периода. Статистическую обработку проводили с помощью программ Microsoft Excel 2013 и Statistica for Windows 6.0. При сравнении групп по клиническим результатам определяли относительный риск (ОР), отношение шансов (ОШ), для которых рассчитывали доверительные интервалы (95 % ДИ). В зависимости от значений ДИ определяли статистическую значимость полученных результатов. Результаты. В течение первых 7 дней в группе сравнения зафиксировали 34 случая ателектазирования легких (67 %). В группе исследования ателектазы легочной ткани развились у 9 пациентов (23 %). Анализ клинических результатов показал, что при применении СС отмечают статистически значимое снижение риска развития ателектазов в первую неделю послеоперационного периода (ОР = 0,346, 95 % ДИ [0,189; 0,634], p = 0,0006). Отношение шансов развития ателектазов в группе исследования статистически значимо ниже по сравнению с группой ретроспективной части исследования (ОШ = 0,150, 95 % ДИ [0,058; 0,386], p = 0,0001). Выводы. Побудительная спирометрия – эффективный способ профилактики ателектазирования легочной ткани у пациентов с умеренным или высоким риском развития послеоперационных легочных осложнений по шкале ARISCAT после оперативных вмешательств на верхнем этаже брюшной полости.
Спонукальна спірометрія як спосіб запобігання розвитку ателектазів легеневої тканини
Побудительная спирометрия как способ предупреждения развития ателектазов легочной ткани
Keywords: spirometry; pulmonary atelectasis; postoperative pulmonary complications; спірометрія; післяопераційні легеневі ускладнення; легень ателектази; побудительная спирометрия; легких ателектазы; послеоперационные легочные осложнения